Impact of Metropolitan City Area Development on Fiscal Performance of 10 Metropolitan Cities In Indonesia - Suharsih, Sri; Winarti, Asih Sri (RSF Conference Series: Business, Management and Social Sciences, 2021)
The Medium-Term Development Plan (RPJMN) 2020-2024 has formulated efforts to optimize the development of the Metropolitan Area so that it is right on target to support inclusive economic growth and equity, which is directed at several indicators. Indicators that are quite important in the development of metropolitan areas are indicators of economic growth and development financing. In this regard, to support the development of the metropolitan area, this study will analyze the financial performance of the metropolitan area and the impact of the development of the metropolitan area on the regional financial performance of each metropolitan area. This research is very important because, in addition to developing metropolitan areas as a development priority in the 2020-2025 RPJMN, this study will analyze the impact of developing metropolitan areas on the fiscal capacity of 10 metropolitan areas using elasticity analysis. It is hoped that the development of the metropolitan area by the government will not only increase the regional economy through GRDP, which in turn can improve the fiscal performance of the metropolitan city area so that it becomes an independent region and does not depend on the central government.